Kotmāi wadūai kānkhūapkhum ʻākhān læ kotmāi wādūai kānkhut læ thom thīdin (Samnak Khūapkhum læ Trūats̨ōp ʻĀkhān, Krom Yōthāthikān læ Phang M̄ưang, 2004)
Thai laws on buidling control and land fillings.